Eighty-three per cent of elite athletes return to preinjury sport after anterior cruciate ligament reconstruction: a systematic review with meta-analysis of return to sport rates, graft rupture rates and performance outcomes. Issue 2 (21st February 2017) - Lai, Courtney C H; Ardern, Clare L; Feller, Julian A; Webster, Kate E
Abstract : Objectives: The primary objective was to calculate the rate of return to sport (RTS) following anterior cruciate ligament (ACL) reconstruction in elite athletes. Secondary objectives were to estimate the time taken to RTS, calculate rates of ACL graft rupture, evaluate postsurgical athletic performance and identify determinants of RTS. Design: Pooled RTS and graft rupture rates were calculated using random effects proportion meta-analysis. Time to RTS, performance data and determinants of RTS were synthesised descriptively. Data sources: MEDLINE, EMBASE, AMED, CINAHL, AMI, PEDro, SPORTDiscus and The Cochrane Library were searched from inception to 19 January 2016. Hand searching of 10 sports medicine journals and reference checking were also performed. Eligibility criteria for selecting studies: Studies were included if they reported the ratio of elite athletes who returned to their preinjury level of sport following ACL reconstruction. Twenty-four studies were included. Results: The pooled RTS rate was 83% (95% CI 77% to 88%). The mean time to RTS ranged from 6 to 13 months. The pooled graft rupture rate was 5.2% (95% CI 2.8% to 8.3%). Six out of nine studies that included a noninjured control group found no significant deterioration in athletic performance following ACL reconstruction. Indicators of greater athletic skill or value to the team were associated with RTS. Summary and conclusions: Eighty-three per cent of elite athletes returned to sport following ACL reconstruction, while 5.2% sustained a graft rupture. Most athletes who returned to sport performed comparably with matched, uninjured controls. This information may assist in guiding expectations of athletes and clinicians following ACL reconstruction.